(untitled) - Labovitz, George H. (New York, 1997)
Presents a breakthrough concept in clear and applicable terms, with an abundance of perspectives and examples from the field. The authors detail how to use alignment to simultaneously link the elements core to your business in a much more focused way and revitalize your organization's strategy, operations, and results.
Keywords: Organizational change,Strategic planning,Information technology,Competition,Thay đổi cơ cấu tổ chức,Kế hoạch chiến lược,Công nghệ thông tin,Sự cạnh tranh; Management,Quản trị